The Transparency Tax - Woods, Andrew K. (2018)
Transparency is critical to good governance, but it also imposes significant governance costs. Beyond a certain point, excess transparency acts as a kind of tax on the legal system. Others have noted the burdens of maximalist transparency policies on both budgets and regulatory efficiency, but they have largely ignored the deeper cost that transparency imposes: it constrains one’s ability to support the law while telling a self-serving story about what that support means. Transparency’s true tax on the law is the loss of expressive ambiguity. In order to understand this tax, this Article develops a taxonomy of transparency types. Typically, transparency means something like openness. But openness about what—the law’s obligations? The reasons for the obligations? The actors behind the law? And open to whom? These are different aspects of what we typically lump together and call “transparency,” and they present different tradeoffs. With these tradeoffs in mind, we can begin to make more informed choices about how to draw the line between maximal and minimal transparency. Of particular note is the finding that we can demand maximal transparency about the law’s obligations without incurring much of the transparency tax. This runs contrary to the soft law literature, which suggests that vagueness about obligation is less costly than the alternative. The Article concludes with a guide for thinking through future transparency tradeoffs